The Intermediatory Role of Microfinancing: Creating Sustainability and Enhancing Agripreneurship in Developing Countries (Journal of Business Management and Accounting, 2018)
With GDP growth rate of 8.99% agriculture, contributes 24% to the Nation’s GDP while the entrepreneurial sector contributes 47%, improving the economic base through agri-preneurship is achievable. The study thus examines, ‘the intermediatory role of Microfinancing, creating sustainability and enhancing agri-preneurship in developing countries’ through a descriptive survey, with questionnaire administered to 80 purposively selected long-time microfinance banks from 2 geo-political zones. Findings indicated that microfinance banks are closer to the grassroot, yet its financial inclusion does not embrace agriculture; very sparse microfinance presence in rural areas, and agro-policy of micro-finance banks should be all-inclusive. Persistent inflation affects the value of loan (Mean 3.1667); Relationship exists between microfinancing and customer growth with 62.3% correlation which is significant at 5% level. Equally, a positive relationship subsists between microfinancing and agri-preneurship depicting a possible link for agripreneurship Vision 2020. The study recommended that new microfinance strategies that can enhance economic growth must be seriously pursued. Efficient linkage to stakeholders within and outside the microfinance system require best practises by managers. Microfinancing targeted at rural agri-preneurship development is suggested